Effect of Kithul Palm (Caryota urens) Fiber on Subjective Satiety and Food Intake of Normal and Overweight Women in Sri Lanka (International Journal of Scientific Research and Management (IJSRM), 2021)
Dietary fiber plays prominent role in satiety characteristics of meals. Kithul palm flour is a conventional food ingredient consumed in Sri Lanka, believed having superior satiety characteristics. This study aimed to find the subjective satiety characteristics of Kithul flour meal compared to soluble fiber meal (Psyllium) and low fiber meal. Three arm, single blinded, cross over placebo controlled study was designed with three isocaloric treatments (carbohydrate 55%, fat 30% and protein 15%) having same energy density ( 1 kcal/g). Satiety characteristics after ingestion of treatment meal were recorded using Visual Analog Scale (VAS). The Kithul flour meal had significant reduction in hunger (P=0.0025), increment in fullness (P=0.0408), reduction in desire to eat (P<0.0001), and reduced prospective food consumption (P<0.0001) values compared to the Psyllium meal. Further, Kithul flour meal had increased fullness (P=0.0388), reduced desire to eat (P=0.0002), and reduced prospective food consumption (P<0.0001) compared to the low-fiber control meal. Kithul flour meal showed superior satiety results in overweight women compared to normal weight women.